Modelling Non-Wood Forest Products in Europe: a review - Calama Sainz, Rafael; Tome, Margarida; Sánchez-González, M.; Miina., J.; Spanos, K.; Palahi, Marc (Forest Systems, 2010)
Non-wood forest products (NWFP) like cork, edible mushrooms, pine nuts, acorns, resins, medicinal plants, and floral greens, among others, provide important recreational and commercial activities in the rural forested areas of the world, being in certain regions more profitable than traditional timber harvesting. Despite the importance of non-wood forest products and services, forest management and planning methods and models in Europe have been traditionally wood oriented, leading to a lack for tools helping forest management based on optimizing these products. In the present work we’ll show and discuss the main factors and challenges limiting the development of classical empirical models for NWFP, and we will review the existing models for the main NWFP in Europe: cork, pine nuts, berries, mushrooms and resins.